Analysis of a Balanced Short Circuit on a Sulbagsel Electrical System by Using The FFA-ABC Method Approach - Haripuddin Haripuddin; Al Imran; Zulhajji Zulhajji; Muliaty Yantahin (Journal of Applied Engineering and Technological Science (JAETS), 2023)
Fault studies are an important part of electrical power system analysis. The purpose of this study was to determine the amount of line current at the point of disturbance when a three-phase balanced fault occurs in the real Sulbagsel electrical system. In this paper, a new hybrid FFA-ABC (Fruit Fly Algorithm-Artificial Bee Colony) method is proposed, which is one of the new methods used to calculate balanced three-phase short circuit currents in electric power systems, especially in the real Sulbagsel electrical system of South Sulawesi, Indonesia. The real electricity system of Sulbagsel was chosen as the research object because this system consists of 15 generators, 44 buses, 52 transmission lines, and 29 load buses with system voltages varying from 30 kV, 70 kV, 150 kV, and 275 kV so that this system is included in the complex system category. To test the effectiveness of the proposed FFA-ABC method, it was implemented on a real electric power system, namely the Sulbagsel System.  In addition, it can also be applied to IEEE electrical systems or other real electric power systems. The results of the new hybrid FFA-ABC method of the balanced short circuit analysis of the Sulbagsel electrical system are then compared using the FFA method, the ABC method, and the deterministic method (in this case, the bus impedance matrix (BIM) method). The simulation results obtained show that the FFA-ABC hybrid method is able to solve the problem of balanced short circuit analysis in the Sulbagsel electrical system in South Sulawesi, Indonesia which the largest fault current occurs when the fault is close to the slack bus generator (bus 2=Sidrap) of 18.9697 p.u, and the smallest fault current occurs when the fault is farthest from the slack bus generator (bus 44=Poso) of  0.8457 p.u.